Towards Higher Psychometric Properties: Testing the Psychological Strain Scales with Larger Samples. Issue 2 (3rd April 2022) - Zhang, Jie; Wang, Wei; Huen, Jenny Mei Yiu; Lyu, Juncheng; Lew, Bob
Abstract: This study aimed to further test the psychometric properties of the Psychological Strain Scales (PSS) with larger samples. A cluster sampling method was employed to recruit 13, 250 college students from seven provinces in China. Descriptive statistics, item statistics, Cronbach's alpha, factor analysis, and correlation analysis were evaluated. Cronbach's alpha coefficient was 0.958 and Guttman's split-half coefficient was 0.866. All the item-total correlations were larger than 0.45 except one. Results from Exploratory Factor Analysis and Confirmatory Factor Analysis supported the four dimensions of psychological strains (value strain, aspiration strain, deprivation strain, and coping strain). The PSS was strongly correlated to the Depression, Anxiety, and Stress Scale (DASS-21), which was commonly used to measure risk for suicide and was predictive ofsuicidality as measured by the SBQ-R. The PSS was a self-report instrument with high reliability and validity which could be applied for extensive use in research to measure psychological strains. Highlights: This is the first study testing the psychometric properties of the PSS in an unusually large sample. Confirmatory factor analysis was applied to provide empirical evidence to the four-factor structure of the PSS. Psychological strains were found to be significantly correlated with depression, anxiety, and stress symptoms and predictive of suicidality.